2014
DOI: 10.3109/1547691x.2014.882449
|View full text |Cite
|
Sign up to set email alerts
|

Pattern recognition scavenger receptor A/CD204 regulates airway inflammatory homeostasis following organic dust extract exposures

Abstract: Exposure to agriculture organic dusts, comprised of a diversity of pathogen-associated molecular patterns, results in chronic airway diseases. The multi-functional class A macrophage scavenger receptor (SRA)/CD204 has emerged as an important class of pattern recognition receptors with broad ligand binding ability. Our objective was to determine the role of SRA in mediating repetitive and post-inflammatory organic dust extract (ODE)-induced airway inflammation. Wild-type (WT) and SRA knockout (KO) mice were int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 35 publications
(71 reference statements)
3
26
0
Order By: Relevance
“…In the present study, we investigated whether high dietary supplementation with vitamin D would reduce airway inflammatory responses following three weeks of daily, repetitive inhalant exposure to ODE or LPS. Consistent with previous work [10, 21], repetitive ODE treatment resulted in significant increases in total cell influx including neutrophils, macrophages, and lymphocytes (Figure 1). Repetitive treatment with LPS also resulted in significant increases in total cell influx including neutrophils, and lymphocytes as compared to saline, but to a significantly lesser magnitude as compared to ODE treatment (Figure 1).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we investigated whether high dietary supplementation with vitamin D would reduce airway inflammatory responses following three weeks of daily, repetitive inhalant exposure to ODE or LPS. Consistent with previous work [10, 21], repetitive ODE treatment resulted in significant increases in total cell influx including neutrophils, macrophages, and lymphocytes (Figure 1). Repetitive treatment with LPS also resulted in significant increases in total cell influx including neutrophils, and lymphocytes as compared to saline, but to a significantly lesser magnitude as compared to ODE treatment (Figure 1).…”
Section: Resultssupporting
confidence: 92%
“…Aqueous ODE was collected and prepared as previously described [11, 21]. Briefly, settled surface dust samples (~3 feet off ground) from swine confinement animal feeding operations (~500–700 animals) were collected and 1 gm was placed into sterile Hank’s Balanced Salt Solution (10 ml; Sigma, St. Louis, MO), incubated for one hour at room temperature, and centrifuged for 20 minutes at 2000 x g .…”
Section: Methodsmentioning
confidence: 99%
“…It was also shown that the adaptor protein myeloid differentiation factor 88 (MyD88), which is utilized by all TLRs (except TLR3) and IL-1R/IL18R, plays a central role, because mice deficient in MyD88 were nearly completely protected against swine facility dust extract-induced acute airway inflammatory responses (35). Scavenger receptors might also represent an important pathway as researchers reported that scavenger receptor A (CD204) deficient mice had increased airway inflammatory consequences to organic dust extract treatment (37). Next, a study of swine confinement workers in Canada found that polymorphisms of the TLR2 gene were associated with improved lung function; polymorphisms in the TLR4 gene were not associated with lung function changes (38).…”
Section: Resultsmentioning
confidence: 99%
“…Dust was collected from raised surfaces of hog confinement facilities and an aqueous extract prepared as previously detailed (Dusad et al, 2013; Poole et al, 2014). The dust was made into an aqueous extract (HDE; hog barn dust extract) by vortexing 1g/ml of dust into Hank’s balanced salt solutions (HBSS) for 1 min and allowed to sit for 1 hr.…”
Section: Methodsmentioning
confidence: 99%